ANALYSIS OF THE EMPLOYABILITY OF ACCOUNTING SCIENCE GRADUATES FROM THE PRIVATE UNIVERSITY OF THIS BRANCH CIUDAD DEL ESTE - Andrés Paniagua, Edwin; Ugarte Silvero, Jazmín; Villagra, Jazmín; Mabel González Pedrozo, Carmen; Vanessa Ruiz Díaz de Salvioni, Viviana (Revista Gênero e Interdisciplinaridade, 2023)
The “Analysis of the employability of graduates of Accounting Sciences from the Universidad Privada del Este Branch Ciudad del Este” is an exhaustive study that examines the employment situation of graduates of the Accounting Sciences degree from the Universidad Privada del Este Branch Ciudad del Este . The main objective of the study is to evaluate the effectiveness of the training provided by the university and improve the quality of education provided. The study was carried out through a survey of graduates of the university’s Accounting Sciences program, as well as employers and experts in the field of accounting. The results of the study revealed that the majority of graduates of the Accounting Sciences degree from the Universidad Privada del Este Branch Ciudad del Este are employed in the field of accounting and finance, and that the majority of them are satisfied with their work. However, some areas for improvement in the training provided by the university were also identified, such as the need to improve soft skills training and the need to offer more internship opportunities. Furthermore, it is recommended that the university improve its career guidance programs to help students make more informed decisions about their career choice and be better prepared to face the demands of the future labor market. In summary, the “Analysis of the employability of Accounting Sciences graduates from the Universidad Privada del Este Branch Ciudad del Este” is an important study that offers valuable recommendations to improve the quality of education provided by the university and the employability of its graduates.